The role of unintegrated DNA in HIV infection - Sloan, Richard D (BioMed Central, 2011)
Integration of the reverse transcribed viral genome into host chromatin is the hallmark of retroviral replication. Yet, during natural HIV infection, various unintegrated viral DNA forms exist in abundance. Though linear viral cDNA is the precursor to an integrated provirus, increasing evidence suggests that transcription and translation of unintegrated DNAs prior to integration may aid productive infection through the expression of early viral genes. Additionally, unintegrated DNA has the capacity to result in preintegration latency, or to be rescued and yield productive infection and so unintegrated DNA, in some circumstances, may be considered to be a viral reservoir. Recently, there has been interest in further defining the role and function of unintegrated viral DNAs, in part because the use of anti-HIV integrase inhibitors leads to an abundance of unintegrated DNA, but also because of the potential use of non-integrating lentiviral vectors in gene therapy and vaccines. There is now increased understanding that unintegrated viral DNA can either arise from, or be degraded through, interactions with host DNA repair enzymes that may represent a form of host antiviral defence. This review focuses on the role of unintegrated DNA in HIV infection and additionally considers the potential implications for antiviral therapy.